The specific use of a school library - Monroe, Julia Anna (My University, 1904)
Introduction: The relation between the school and literature is an important one. To be sure in Garfield’s conception of a university, a log with himself at one end and Marle Hopkins at the other, books have no place, but we cannot all be blest with an education under so rare a spirit as this. In default we must “patch up” both as pupils and teachers, with that which master minds have left for us on the printed page. Aside from this, each pupil will, sooner or later, come to the place where his further mental training will depend upon himself alone. In this crisis all depends upon his ability to choose for himself, books that will invigorate and quicken his mental powers rather than those that will enervate and deteriorate them. Then too in the development of a child, following roughly the “periods” of Rosencrang, intuitive, imaginative, and logical, if a teacher has means at hand she can more efficiently help a child in his progress.
Citation: Monroe, Julia Anna. The specific use of a school library. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Schools; Libraries; Education; Affect of Libraries on Education; Theses; Manuscripts (documents)